Manajemen Kinerja Guru di Sekolah Menengah Pertama Negeri 1 Karangan Kecamatan Karangan Kabupaten Kutai Timur - Syahrin, Syahrin; Salehudin, Mohammad (El-Idare, 2024)
Teachers play a crucial role in education worldwide, responsible for teaching and guiding students. This research follows a descriptive qualitative method, utilizing interviews, observation, and documentation as data collection techniques. The research subjects involve school principals, teachers, and relevant stakeholders in teacher performance management. The results indicate that teacher performance management at SMP Negeri 1 Karangan has shown positive development through stages of planning, assessment system establishment, supervision, evaluation, and performance improvement. Although performance planning is structured considering the school's vision, mission, and goals, challenges remain regarding performance target setting and resource allocation. Teacher participation in planning is appreciated, but implementation requires refinement. Assessment system establishment is participatory with various methods, although implementation hurdles exist. Performance supervision involves classroom observation, test evaluation, and meetings, yet consistency and accountability need enhancement. Performance evaluation employs diverse methods and instruments, but challenges regarding resources and teacher perceptions persist. Recognition and rewards for performance are appreciated, but structured improvement is needed. Therefore, enhancing education quality requires continuous efforts in improving teacher performance management through collaboration among all relevant parties.